DESCRIPTIONS OF FLUID INTAKE AND HYDRATION STATUS IN PANTI SOSIAL TRESNA WERDHA MULIA DHARMA KUBU RAYA REGENCY - ., Vini Cahyani (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Dehydration has been linked with high morbidity andmortality. During aging process, many physiological changes put theelderly at greater risk of dehydration. Decreasing sensation of thirsty cancaused low fluid consumption in elderly and they may be purposely restrictthe consumption in manner to lower frequency of urination. Maintaininghydration is essential for elderly health. Objective: The purpose of thisresearch was to determine distribution of fluid intake and hydration statusin elderly who lived in Panti Sosial Tresna Werdha Mulia Dharma KubuRaya Regency. Method: This research was descriptive study with crosssectional approach. Data were collected from 41 elderly people aged 6079years old. Data were recruited with consecutive sampling technique.This research was implemented in Panti Sosial Tresna Werdha MuliaDharma Kubu Raya on February 2014. Fluid intake was measured by foodfrequence quesioner (FFQ) and hydration status was detected by urinchart. Result: There were 65,4% elderly with inadequate fluid intake and61% elderly had dehydration, among them were 34,1% male and 26,8%female with dehydration, dehydration occurred in 4,9% elderly withmalnutrition, 29,3% in elderly with risk of malnutrion and 26,8% in elderlywith normal status nutrition. Conclusion: Inadequate fluids intake canevoke dehydration in elderly. It makes fluid consumption should beseriously noted, hydration status can be monitored by using urin chart.Keywords: fluid, dehydration, elderly1) Medical School, Faculty of Medicine, Tanjungpura University Pontianak, West Kalimantan2) Department of Community Medicine, Family and Public Health, Medical School, Faculty of Medicine, Tanjungpura UniversityPontianak, West Kalimantan 3) Department of Parasitology, Faculty of Medicine, TanjungpuraUniversity Pontianak, West Kalimantan